Efek Berita mengenai COVID-19 terhadap Harga Saham di Indonesia - Saraswati Dyah Pramuji (Seminar Nasional Official Statistics, 2021)
Information from the media can be one of the considerations for investors in investing stocks, so the role of the media is very meaningful in determining stock price movements. This study aims to analyze the long and short term influence of media coverage related to COVID-19 on stock prices in Indonesia during the economic recovery from April to May 2021 using Error Correction Mechanism (ECM). The results show that the infodemic index variable and the number of deaths due to COVID-19 have a negative effect on stock prices in the long term. The media hype index variable and the number of deaths due to COVID-19 have a negative effect on stock prices in the short term. Meanwhile, the sentiment index and panic index variables have no effect on stock prices, both in the long and short term. It is known that the number of deaths due to COVID-19 has a negative effect on stock prices in the long and short term, so that the proper handling of COVID-19 to lower the death rates can improve the investment climate in this economic recovery period.